Smart walker based IoT physical rehabilitation system - Nave, C.; Postolache, O. (2018 International Symposium in Sensing and Instrumentation in IoT Era, ISSI 2018, 2018)
This paper describes the development of an IoT Physical Rehabilitation solution based on Smart Walkers. Multimodal sensing solution including IMU, Load Cells and Ultrasound sensor was designed and implemented. The smart walker is characterized by Arduino Mega computation platform that performs the calculation of walking metrics during a rehabilitation session and stores them in the cloud. The data analysis and data visualization is supported by an implemented website and mobile app. Experimental results performed with healthy volunteers and appropriate data analysis are included in the paper.